Virus del "Marchitamiento manchado del tomate" en cultivos de papa de Mendoza - Pontis, Rafael E. (1962)
Tomato spotted wilt virus on potato crops in Mendoza. A mixed natural infection on tomato spotted wilt virus (Lethum australiense H.)potato virus X (Annulus dubius H.) and potato virus Y (Marmor upsilon H.) was discovered among potato field plantings (Solanum tuberosum L. var. Up-to-Date). The identity of these viruses was established through experimental evidence. This is the first time that the tomato spotted wilt virus has been determined on potato crops in Mendoza.